Study on The Preparation of Barangan Banana Peel and Chocolate Jam - Deannisa Matondang; Zulkifli Lubis; Mimi Nurminah (Jurnal Rekayasa Pangan dan Pertanian, 2014)
The research was aimed to study on the preparation of barangan banana peel chocolate jam that is one alternative for the development of functional food products.. The reseach had been performed using factorial completely randomized design, with two factors i.e : the ratio of barangan banana peel and chocolate powder (M) : 95%:5%, 90%:10, 85%:15%, 80%:20% , and pectin concentration (P) : 0,25%, 0,5%, 0,75%, 1%. Parameters analyzed were water content (%), ash content (%), fat content (%),vitamin C content (mg/100g bahan),total soluble solid (oBrix), stickiness and organoleptic values (colour, flavor, and taste). The result showed that the ratio of barangan banana peel and chocolate powder and pectin concentration had highly significant effect on water content, ash content, fat content, total soluble solid, stickiness and organoleptic values (colour, flavor, and taste). The pectin concentration had highly significant effect on water content, ash content, total soluble solid, stickiness and organoleptic values (colour and taste). The interaction of the two factors had significant effect on water content and had highly significant effect on ash content. The ratio of banana peel and chocolate powder of 95% : 5% and pectin concentration of 1% produced the best quality of barangan banana peel chocolate jam. Keyword : banana peel, jam, pectin